Autologiczny przeszczep naczyniówki i nabłonka barwnikowego siatkówki w leczeniu krwotoku podsiatkówkowego w przebiegu zwyrodnienia plamki związanego z wiekiem - Stopa, Marcin; Rospond-Kubiak, Iwona; Rakowicz, Piotr; Kocięcki, Jarosław (Klinika Oczna / Acta Ophthalmologica Polonica, 2010)
Purpose: To report autologous choroidal RPE patch transplantation for treatment of submacular hemorrhage in a patients with age related macular degeneration. Material and methods: A case report of a patient with sudden vision deterioration due to submacular hemorrhage in AMD. The visual acuity was 5/5 in the right eye and 0.5/50 in the left eye. He was treated with autologous choroidal RPE patch transplantation. Outcome measures included preoperative and postoperative visual acuity at 1, 3, 6 months, duration of hemorrhage, hemorrhage size on preoperative fluorescein angiography and thickness of the subretinal hemorrhagic complex on preoperative and postoperative OCT scans. Results: Visual acuity improved from 0.5/50 to 5/50 in 6 months follow-up. No major intraoperative and postoperative complications were observed. The perfusion of the graft was confirmed in ICG angiography. Conclusions: Autologous choroidal RPE patch transplantation is an effective option for submacular hemorrhage treatment in AMD. Unlike macular translocation, the surgery can be performed even in patients with excellent visual acuity in the fellow eye.